1996
DOI: 10.1080/00150193.1996.10399434
|View full text |Cite
|
Sign up to set email alerts
|

INDUCED POLARIZATION IN THE SmA*-PHASE: A COMPARISON OF THEORETICAL MODELS AND EXPERIMENTAL METHODS

Abstract: When measuring the po larization of a ferroelectric liquid crystal one usually obtains quite a pronounced tail P(T) going well into the SmA *-phase. If this is a manifestation of the elcctrodinic effect one would, at first thought, expect it to scale as P-(T-Tct and as P-E. In reality, however, it scales like P-( T-Tc ( and P-£ 3 . In order to find out whether this is consistent with the Landau description of the transition one has to check the precise character of the quantity P actually furnished by the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…discussion outlined in the previous section indeed clearly applies to the experimental situation: In the nonirradiated state P s (T) continuously decreases to zero, reflecting the second-order nature of the ferroelectric smectic C* -A* transition at about T c Ϸ327 K. The slight tailing of the P s (T) curve into the paraelectric Sm-A* phase originates from the nonlinearity of the electroclinic effect that is induced by the electric field which we applied to measure the spontaneous polarization. 26 Upon irradiation the phase transition is considerably shifted through the secondary photoferroelectric effect to about T c ЈϷ325 K. If we now shift the P s (T) curve of the nonirradiated state to the new T c Ј ͑dotted line in Fig. 3͒, we still observe a clear difference compared to the P s (T) actually measured in the irradiated state.…”
Section: Photoferroelectricity In Sm-c* Liquid Crystalsmentioning
confidence: 84%
“…discussion outlined in the previous section indeed clearly applies to the experimental situation: In the nonirradiated state P s (T) continuously decreases to zero, reflecting the second-order nature of the ferroelectric smectic C* -A* transition at about T c Ϸ327 K. The slight tailing of the P s (T) curve into the paraelectric Sm-A* phase originates from the nonlinearity of the electroclinic effect that is induced by the electric field which we applied to measure the spontaneous polarization. 26 Upon irradiation the phase transition is considerably shifted through the secondary photoferroelectric effect to about T c ЈϷ325 K. If we now shift the P s (T) curve of the nonirradiated state to the new T c Ј ͑dotted line in Fig. 3͒, we still observe a clear difference compared to the P s (T) actually measured in the irradiated state.…”
Section: Photoferroelectricity In Sm-c* Liquid Crystalsmentioning
confidence: 84%
“…47 Due to the coupling between P S and h, the temperature dependence of P S near T C should also reflect the nature of the SmA*-C* phase transition. However, P S measurements by integration of polarization reversal current peaks are complicated by induced polarization contributions near T C due to the electroclinic effect (soft mode), 48 although the latter can often be minimized by using low triangular ac fields. The P S (T 2 T C ) plot for the 5 mol% mixture of 3a in 2-PhP (Fig.…”
Section: Spontaneous Polarization Measurementsmentioning
confidence: 99%
“…To compare our results with experimental measurements of the polarization as a function of electric field, we must take into account one subtlety of the experiments. As shown by Ruth et al [19,20], the polarization observed experimentally (by the triangle-wave technique or other techniques) is not the total polarization conjugate to the electric field. Rather, it is a specific nonlinear component of the polarization, which can be written as…”
Section: Finite Cells Under An Electric Fieldmentioning
confidence: 93%
“…As shown by Ruth et al [19,20], the polarization observed experimentally (by the triangle-wave technique or other techniques) is not the total polarization conjugate to the electric field. Rather, it is a specific nonlinear component of the polarization, which can be written as…”
Section: Finite Cells Under An Electric Fieldmentioning
confidence: 94%